A STUDY ON ACCEPTANCE SPEECHES OF AMERICAN AND VIETNAMESE AWARDEES AT MOVIE AWARD CEREMONIES = Nghiên cứu về bài phát biểu nhận giải của người Mỹ và người Việt Nam trong các lễ trao giải thưởng điện ảnh - Nguyễn, Thị Kim Huệ (2020)
The main purpose of the study is to reveal some similarities and differences in acceptance speeches made by American and Vietnamese people at movie award ceremonies. The paper first presents theoretical background on some relating issues including public speaking, politeness and speech acts, with a view to supporting ideas for the later analysis. Then the paper goes further into the procedure of collecting and analyzing data. The qualitative method is employed as the main tool to conduct the research. Data are collected from 20 American and 20 Vietnamese acceptance speeches in movie award ceremonies from 2009 to 2014. A detailed investigation and analysis of the format, thanking strategies and language use in acceptance speeches has been conducted. Results of the study illustrate certain similarities and differences in American and Vietnamese speakers. In addition, the results state that cultural factors, especially the assumptions of formality in two cultures affect significantly those differences.